Quality Control of Civil Engineering Laboratory Testing Systems Based On The Development of Standard Operating Procedures (SOPs) and Standardized Testing Forms - Ely Mulyati; Muhammad Alvin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The quality of laboratory testing services is a critical factor in supporting educational, research, and community service activities in higher education institutions. However, the Civil Engineering Laboratory faced challenges related to the absence of standardized testing procedures and uniform documentation systems, which could affect the consistency and traceability of testing activities. This community service program aimed to strengthen the laboratory quality control system through the development and implementation of Standard Operating Procedures (SOPs) and standardized testing forms. The assistance methods included field observation, needs assessment, document review, mentoring, consultation, and participatory development of quality documents. The activities focused on identifying existing testing practices, designing SOPs for laboratory operations, and developing standardized forms for recording and documenting testing results. The results showed that the laboratory successfully adopted a set of SOPs and standardized testing forms that support consistent testing procedures, improve documentation quality, and enhance data traceability. In addition, laboratory personnel gained a better understanding of quality management principles and standardized documentation practices. The implementation of these documents contributed to improving operational efficiency, reducing administrative errors, and supporting continuous quality improvement within the Civil Engineering Laboratory.